The open road ebook 50 best road trips in the usa. - Dunham, Jessica (Moon Travel Guide., 2020)
Get inspired and get ready to hit the road with the ultimate guide to America's best road trips! The Open Road: 50 Road Trips in the USA features: Strategic lists and road trip options: Choose from lists of the best coastal drives, cross-country journeys, trips for kids, awe-inspiring views, and more Flexible itineraries: 50 different road trips organized by region gear you up for any adventure, from a weekend getaway to a cross-country trip Can't-miss stops from coast to coast: Leaf-peep along the Blue Ridge Parkway, look for wildflowers on Arizona's Apache Trail, or gaze at the mysterious Marfa Lights blinking over the West Texas desert. Snap selfies with kitschy roadside attractions along Route 66, cross the Continental Divide in Colorado, and fall asleep to the sound of crashing waves at your campsite in Big Sur The best local flavors: Eat your way through Vermont's farms, dairies, orchards, and maple houses or indulge in gulf shrimp and fried okra in the South. Sample oysters and craft beers in Oregon or stop for shave ice along the scenic Oahu Coastal Loop Expert advice from seasoned road-tripper Jessica Dunham Comprehensive planning resources: Easy-to-use maps, helpful info on things to do, lodging, and dining for every route, clear directions to each route's starting point, and tips for minimizing your environmental impact along the way Gorgeous, full-color photos and a fold-out map Essential tips for health and safety on the road, navigating weather conditions, strategies for road-tripping with kids and four-legged friends, and playlists and podcasts to soundtrack your adventure Whether you're hugging the coast or driving the Loneliest Road, find your adventure with The Open Road: 50 Road Trips in the USA .  For more in-depth information on a specific road trip, check out Moon's bestselling road trip guides.